Answer:
The answer is 0.71 per ounce.
Step-by-step explanation:
You can use proportions to solve this.
![\frac{89.95 dollars}{64lb} = \frac{1 dollar}{x} \\64 * 1 = 64\\89.95 * x = 89.95x\\\\\frac{64}{89.95} = \frac{89.95x}{89.95}\\\\0.7115063924 = x\\Which when rounded to the nearest hundredths is:\\0.71](https://tex.z-dn.net/?f=%5Cfrac%7B89.95%20dollars%7D%7B64lb%7D%20%3D%20%5Cfrac%7B1%20dollar%7D%7Bx%7D%20%5C%5C64%20%2A%201%20%3D%2064%5C%5C89.95%20%2A%20x%20%3D%2089.95x%5C%5C%5C%5C%5Cfrac%7B64%7D%7B89.95%7D%20%3D%20%5Cfrac%7B89.95x%7D%7B89.95%7D%5C%5C%5C%5C0.7115063924%20%3D%20x%5C%5CWhich%20when%20rounded%20to%20the%20nearest%20hundredths%20is%3A%5C%5C0.71)
Drawing this square and then drawing in the four radii from the center of the cirble to each of the vertices of the square results in the construction of four triangular areas whose hypotenuse is 3 sqrt(2). Draw this to verify this statement. Note that the height of each such triangular area is (3 sqrt(2))/2.
So now we have the base and height of one of the triangular sections.
The area of a triangle is A = (1/2) (base) (height). Subst. the values discussed above, A = (1/2) (3 sqrt(2) ) (3/2) sqrt(2). Show that this boils down to A = 9/2.
You could also use the fact that the area of a square is (length of one side)^2, and then take (1/4) of this area to obtain the area of ONE triangular section. Doing the problem this way, we get (1/4) (3 sqrt(2) )^2. Thus,
A = (1/4) (9 * 2) = (9/2). Same answer as before.
The formula of compound continuously is
A=p e^rt
A future value?
P present value 300
R interest rate 0.07
T 4 years
E constant
A=300×e^(0.07×4)
A=396.94 round your answer to get
A=397
Answer:
Step-by-step explanation:
As we move from the x-intercept (-2, 0) to the y-intercept (0, 4), x increases by 2 (this is the run) and y by 4 (this is the rise). Thus, the slope of this line is
m = rise/run = 4/2 = 2.
Given the y-intercept (0, 4) and the slope (2), the slope-intercept form of the equation of this line is y = 2x + 4.
From this we get the point-slope form:
y = 2x + 4 becomes y - 4 = 2(x - 0), or just y - 4 = 2x.
Answer:
0.18181818181
Step-by-step explanation: